IMPLEMENTASI FUZZY INFERENCE SYSTEM (FIS) METODE TSUKAMOTO PADA SISTEM PENDUKUNG KEPUTUSAN PENENTUAN KUALITAS AIR SUNGAI - Galuh Mazenda; Arief Andy Soebroto; Candra Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2014)
Water was one resource that has a very important function for life and human life. River was the main channel as water flowing from upstream to downstream, has many domestic and industrial activity along the stream. The flow dynamics lead to changes in the quality and quantity of the river significantly. Water quality was maintained by analyzing the quality of the river water. Decision Support System (DSS) was a system designed to simplify the determination of water quality officer in making decisions. Inputs are parameter water quality test that consists of physical parameters and chemical parameters.The process of water quality analysis was conducted using Fuzzy Inference System Tsukamoto method. Fuzzy tsukamoto method used to determine the water quality of the river into four (4) classes which meet quality standards (good condition), lightly polluted, contaminated medium, and heavy polluted. The results of tested scenarios obtained an accuracy rate between the results of the calculation method of Fuzzy Tsukamoto with the calculated water quality STORET method at 90%.